Nandi in the Papvimochneshwar Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Nandi, the divine bull, is the vahana (vehicle) of Lord Shiva. Nandi serves as the gatekeeper to the sanctum, symbolizing loyalty and unwavering devotion. The marble Nandi statue is placed directly facing the lingam in the garbhagriha (sanctum sanctorum).